1999
DOI: 10.1007/s002590050497
|View full text |Cite
|
Sign up to set email alerts
|

”Ecstasy"-induced changes of cerebral glucose metabolism and their correlation to acute psychopathology

Abstract: The aim of this study was to determine the acute effects of the "Ecstasy" analogue MDE (3,4-methylene dioxyethamphetamine) on cerebral glucose metabolism (rMRGlu) of healthy volunteers and to correlate neurometabolism with acute psychopathology. In a randomized double-blind trial, 15 healthy volunteers without a history of drug abuse were examined with fluorine-18-deoxyglucose (18FDG) positron emission tomography (PET) 110-120 min after oral administration of 2 mg/kg MDE (n = 7) or placebo (n = 8). Two minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…Compared to [O-15]water PET for the measurement of cerebral blood flow with a temporal resolution of 10-30 s (Silbersweig et al, 1993), 18-FDG shows a relatively slower temporal resolution of approximately 20 min, which would indicate that 18-FDG is more appropriate for the investigation of 'tonic' stimulation paradigms or pharmacological challenges (Volkow et al, 1990(Volkow et al, , 1999Vollenweider et al, 1998;Gouzoulis-Mayfrank et al, 1999;Schreckenberger et al, 1999). Since the psychophysiological changes under acute alcohol influence are rather tonic, they are not expected to be adequately Table 3b.…”
Section: Methodical Considerationsmentioning
confidence: 99%
“…Compared to [O-15]water PET for the measurement of cerebral blood flow with a temporal resolution of 10-30 s (Silbersweig et al, 1993), 18-FDG shows a relatively slower temporal resolution of approximately 20 min, which would indicate that 18-FDG is more appropriate for the investigation of 'tonic' stimulation paradigms or pharmacological challenges (Volkow et al, 1990(Volkow et al, , 1999Vollenweider et al, 1998;Gouzoulis-Mayfrank et al, 1999;Schreckenberger et al, 1999). Since the psychophysiological changes under acute alcohol influence are rather tonic, they are not expected to be adequately Table 3b.…”
Section: Methodical Considerationsmentioning
confidence: 99%
“…Other studies showed that low 5-HT activity is associated with decreased prefrontal activity, which is necessary for exerting inhibitory or impulse control over behaviour [95]. Thus, low 5-HT and prefrontal activity observed in SDI may explain not only their compulsive drug use, but also several other co-morbid conditions, such as their depressed mood, and antisocial behaviour [100,103].…”
Section: Neuropharmacological Changes Associated With Substance Addicmentioning
confidence: 98%
“…techniques indicating general neuronal metabolic activity. Although some authors have investigated the acute effects of Ecstasy on glucose metabolism and cerebral blood¯ow (Schreckenberger et al, 1998(Schreckenberger et al, , 1999Gamma et al, 2000), this review concentrates on the long-term effects of MDMAinduced 5-HT neurotoxic lesions. (Terriere et al, 1995), has made it possible to assess the density of cortical HT 2A receptors in the living human brain using SPECT (Busatto et al, 1997).…”
Section: Functional Consequences Of Mdma-induced Neuronal Injurymentioning
confidence: 99%